Flood Mitigation Policy Directive in East Lombok Regency West Nusa Tenggara Province - Prasojo, Matur (Sumatra Journal of Disaster, Geography and Geography Education, 2017)
This type of research belongs to the type of descriptive research. The method used in this research is Mixed Methods. Technique of data analysis in this research by using formula determined by criteria and for analysis of data of policy direction of flood mitigation using AHP. Sembalun Sub-district, East Lombok regency is an area with bad land characteristic and supports flood disaster, in terms of flood hazard level included in criteria of moderate flood hazard and has a total level of total risk. Policy priorities that can be considered in decision making in relation to flood mitigation in Sembalun sub-district, East Lombok regency based on 3 criteria that exist using AHP are 1) Based on land characteristic criteria, among others: a) Making permanent embankment, b) Dissemination and disaster simulation flood, c) Provision of flood posts.2) Based on the criteria of disaster response community, among others: a) Establishment of early warning system, b) Disaster flood socialization and simulation, c) Provision of flood posts. 3) Based on the criteria of flood risk level, among others: a) Making permanent embankment, b) Disaster flood socialization and simulation, c) Provision of flood posts and building early warning system.